Propensity score analysis for the efficacy of preoperative antibiotics in patients with resected primary lung cancer: Levofloxacin versus cefazolin - Kenji Tomizawa; Junichi Soh; Hana Oiki; Shota Fukuda; Masaya Nishino; Katsuaki Sato; Tetsuya Mitsudomi (Clinical Surgical Oncology)
Objective: The use of cefazolin (CEZ) is recommended as a preoperative prophylactic antibiotic, but other antibiotics may be used for various reasons. We adopted a fluoroquinolone (levofloxacin; LVFX) as a preoperative prophylactic antibiotic because of reduced supply of CEZ worldwide, while the efficacy of LVFX in preventing infectious complications including surgical site infection (SSI), empyema, and pneumonia has not been fully investigated. Methods: The medical records of 260 patients who underwent primary lung cancer resection between April 2018 and July 2020 were retrospectively reviewed. Eighty-nine patients before May 2019 were intravenously received a single dose of CEZ with additional administration every 3 ​h during surgery (the CEZ group) and 171 patients after that date were orally received a preoperative single dose of LVFX (the LVFX group). The efficacy of preventing infectious complications was compared between two groups. The propensity score matching (PSM) method was also applied to minimize selection bias. Results: Infectious complications were observed in 3.1% (8/260) of patients, with no significant difference between the LVFX group (2.9%) and the CEZ group (3.4%) regardless of subtypes such as SSI and empyema. After PSM, 77 patients each were matched from the two groups, and there was also no significant difference in the incidence of infectious complications (the LVFX group; 2.6% vs. the CEZ group; 3.9%). Conclusion: LVFX has comparable efficacy to CEZ for preventing infectious complications, and may be an alternative to preoperative antibiotics for patients with primary lung cancer who underwent pulmonary resection.